NCOR1 Orchestrates Transcriptional Landscapes and Effector Functions of CD4+ T Cells - Hainberger, Daniela; Stolz, Valentina; Zhu, Ci; Schuster, Michael; Müller, Lena; Hamminger, Patricia; Rica, Ramona; Waltenberger, Darina; Alteneder, Marlis; Krausgruber, Thomas; Hladik, Anastasiya; Knapp, Sylvia; et al. (Frontiers in Immunology, 2020)
The differentiation of naïve CD4+ T cells into T helper (Th) subsets is key for a functional immune response and has to be tightly controlled by transcriptional and epigenetic processes. However, the function of cofactors that connect gene-specific transcription factors with repressive chromatin-modifying enzymes in Th cells is yet unknown. Here we demonstrate an essential role for nuclear receptor corepressor 1 (NCOR1) in regulating naïve CD4+ T cell and Th1/Th17 effector transcriptomes. Moreover, NCOR1 binds to a conserved cis-regulatory element within the Ifng locus and controls the extent of IFNγ expression in Th1 cells. Further, NCOR1 controls the survival of activated CD4+ T cells and Th1 cells in vitro, while Th17 cell survival was not affected in the absence of NCOR1. In vivo, effector functions were compromised since adoptive transfer of NCOR1-deficient CD4+ T cells resulted in attenuated colitis due to lower frequencies of IFNγ+ and IFNγ+IL-17A+ Th cells and overall reduced CD4+ T cell numbers. Collectively, our data demonstrate that the coregulator NCOR1 shapes transcriptional landscapes in CD4+ T cells and controls Th1/Th17 effector functions.